Antioxidative properties analysis of gastrointestinal lactic acid bacteria in Hainan black goat and its effect on the aerobic stability of total mixed ration - Yang, Tianshu; Yang, Jinsong; Tang, Kai; Zhi, Wenbo; Chen, Rong; Tan, Haisheng (Frontiers in Microbiology, 2022)
In this study, lactic acid bacteria strains (HCS-01, HCS-05, HCS-07, HCW-08, HCW-09) derived from the gastrointestinal tract of Hainan black goat were evaluated for their antioxidant capacity in vitro, and the lactic acid bacteria with strong antioxidant capacity were screened for application in improve the aerobic stability of total mixed ration (TMR). The results showed that all the tested lactic acid bacteria had a certain tolerance to hydrogen peroxide. By comprehensively comparing the scavenging abilities of fermentation supernatants, whole cell bacterial suspensions and cell contents of five lactic acid bacteria strains to 2,2-diphenyl-1-picrylhydrazine (DPPH), hydroxyl radicals and superoxide anions, and their antioxidant enzyme activity, it was found that Lactobacillus fermentum HCS- 05 and Lactobacillus plantarum HCW-08 have the strongest comprehensive antioxidant capacity, and their scavenging capacity for various free radicals has reached more than 60%. Using strains HCS-05, HCW-08 and laboratory-preserved Lactobacillus plantarum HDX1 fermented TMR, the fermentation quality and aerobic stability of the feed after 60 days of fermentation were significantly higher than those of the blank treatment group. The effect of mixed strains HCS-05 and HCS-08 for TMR fermentation was the best (P<0.05). At the same time, the fermentation effect of Lactobacillus plantarum HDX1 on TMR was significantly lower than that of the selected lactic acid bacteria from the gastrointestinal tract of Hainan black goats (P<0.05). The results show that the test strain can significantly improve the aerobic stability of the fermented feeds.